Physical-sporting activity, physical self-concept and satisfaction with life. (European Journal of Education and Psychology, 2010)
The relationship between physical-sporting activity and physical self-concept has been well documented. Furthermore, diverse studies also support the finding that physical-sporting activity is linked to satisfaction with life, a relationship which some authors believe to be mediated by physical self-concept. This study aims to verify the way in which these three variables are related. Participants were 408 adults (163 men and 245 women) aged between 23 and 65 (M = 44.82; SD = 13.44), classified into sedentary (37.5%), moderately active (35.4%), active (16%) and very active (11%), depending on metabolic expenditure (expressed as METs) calculated on the basis of frequency x duration x value of the physical activity carried out. The results reveal positive associations between physical-sporting activity and both physical self-concept and satisfaction with life, in the following sense: the more physical-sporting activity engaged in, the better the subject’s self-concept and the greater their satisfaction with life.